A Report On Clinical Mastitis Associated With Pseudopregnancy In A Great Dane Bitch (Applied Biological Research, 2018)
Mastitis is an infrequent condition in canines relative to the scenario of this disease in farm animals  (Schlafer and Miller, 2007). Canine mastitis usually occurs in postpartum period but may also occur  in later stages of pregnancy and pseudopregnancy (Wiebe and Howard, 2009). Usually mastitis is a  disease of bacterial etiology (Orfanou et al., 2008), but parasitic etiology has also been reported (Park  et al., 2007). The main bacterial agents involved are coliforms, Staphylococcus sp. and Streptococcus  sp. (Wiebe and Howard, 2009). Affected animal usually displays general symptoms of fever,  vomiting, dehydration, anorexia, trembling and decreased mothering behaviour. Canine mastitis has  favourable prognosis when there is early diagnosis and appropriate treatment is provided. The  laboratory diagnosis usually includes pH test, cytology and microbiology of milk. There are meagre  reports wherein hematology and biochemistry assays have also been taken into consideration for  mastitis diagnosis (Ververidis et al., 2007; Vasiu et al., 2016). This report describes a case of  pseudopregnancy associated mastitis caused by Klebsiella pneumoniae (K. pneumoniae) in a Great  Dane bitch and its successful therapeutic management.
Keywords: Clinical Mastitis; Pseudopregnancy; Dane Bitch